EFFECTS OF TELMISARTAN ON PLASMA INTERLEUKIN-6 AND C-REACTIVE PROTEIN LEVELS IN MONOSODIUM GLUTAMATE-INDUCED OBESITY IN WISTAR ALBINO RATS - KM, VENKATESH; BS, SRIRAM; V, RAVICHANDRA; HOLLA, RAJENDRA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objectives: The objectives of this study were to evaluate the effects of telmisartan on plasma interleukin (IL)-6 and C-reactive protein (CRP) levels in monosodium glutamate (MSG)-induced obesity in Wistar albino rats. Methods: MSG at the dose of 500 mg/kg body weight is dissolved in distilled water and administered for 22 days. On the 9th day, telmisartan 7.5 mg/kg body weight is administered. After completion of experiment, body weight and biochemical parameters such as plasma IL-6 and CRP levels are measured using enzyme-linked immunosorbent assay. Results: Telmisartan significantly decreased plasma IL-6 and CRP levels in MSG-treated obese rats. Conclusion: Telmisartan, probably through its peroxisome proliferator-activated receptor-γ agonistic activity, produces significant anti-obesity effects in rats and may help in treating obese patients with metabolic syndrome.